Prevalence of Diabetes and Diabetic Retinopathy in a Brazilian Population - Schellini, Silvana Artioli [UNESP]; Carvalho, Geraldo Miranda de [UNESP]; Rendeiro, Fabricio Salles [UNESP]; Padovani, Carlos Roberto [UNESP]; Hirai, Flavio Eduardo (Informa Healthcare, 2014)
Purpose: To evaluate the prevalence of type 2 diabetes mellitus and diabetic retinopathy (DR) in a Brazilian population.Methods: Population-based, cross-sectional study conducted in 9 cities located in the Midwest region of the state of Sao Paulo, Brazil, between 2006 and 2007, including 4690 individuals aged >= 30 years. Diabetes was self-reported and DR was assessed by indirect ophthalmoscopy.Results: The prevalence of type 2 diabetes was 8.68% (95% confidence interval, CI, 7.87-9.48%), and DR was present in 7.62% (95% CI 5.02-10.20%) of participants with self-reported type 2 diabetes. Approximately 35.4% of individuals diagnosed with DR did not know they had diabetes prior to DR diagnosis. Prevalences of low vision and blindness were higher among those with diabetes and DR. Cataract was still a major cause of blindness in this population.Conclusion: This is the first large population-based study on DR in Brazil. High rates of visual impairment were found in persons with type 2 diabetes, but cataract is still one of the main causes of blindness. Large surveys are necessary for public health policy advocacy in developing countries.
Keywords: Blindness; diabetes; epidemiology; prevalence; retinopathy